2015
DOI: 10.5539/ijef.v7n2p144
|View full text |Cite
|
Sign up to set email alerts
|

Historical Analysis of Bank Profitability Using CAMEL Parameters: Role of Ownership and Political Regimes in Pakistan

Abstract: In first sixty years of its existence financial sector of Pakistan has experienced two prominent episodes. One, there was an experimentation with the ownership structure of financial institutions which started with promotion of ownership by the private sector and then in 1970s they were nationalized. Subsequently the process was reversed in the 1990s transferring most of the banking assets back to the private sector. Two, on the political front, for long 33 years autocrat have interrupted the democratic order … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…Our findings (regression results for Admin Expenses to Interest Income and Bank's performance association) are consistent with the studies of Davydenko, Ongore, Sufian and Chong, and Aftab, Samad and Husain [110,115,117,118].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Our findings (regression results for Admin Expenses to Interest Income and Bank's performance association) are consistent with the studies of Davydenko, Ongore, Sufian and Chong, and Aftab, Samad and Husain [110,115,117,118].…”
Section: Discussionsupporting
confidence: 81%
“…There is a very strong relationship between bank performance and the management efficiency through the expenses of management [117]. Management efficiency has a positive influence on the bank profitability; however the impact of only management efficiency is statically significant [118].…”
Section: Gross Advances To Total Deposit Ratiomentioning
confidence: 99%
“…Alshatti (2015) also determined that liquidity ratio is very significant for the banks in order to increase their profitability. In addition to these studies, Aftab et al (2015); Gyamerah and Amoah (2015); and Hu and Xie (2016) determined that effective risk management plays an important role with respect to the profitability of banks.…”
Section: Buchory (2015) Indonesia Regressionmentioning
confidence: 99%
“…For example, even though Bouheni (2013) finds positive impact of supervision on banks’ performance, the effect is limited when the macroeconomic variables are added in the model. Interestingly, Aftab, Samad, and Husain (2015) find the positive relationship of profitability with CAMELS ratings after controlling the effect of some of the macroeconomics variables like GDP and money supply. Further, their study shows positive relation of bank’s profitability with the quality of bank’s assets and management but negative relation with the liquidity and level of capital requirement.…”
Section: Literature Reviewmentioning
confidence: 89%
“…By contrast, Alemu and Aweke (2017) do not find any significant relation in explaining performance of private commercial banks in Ethiopia. In regards to controlling the macroeconomics variables like GDP, Aftab et al (2015) find interesting results. After controlling GDP growth in their study, they found that the asset quality is important for the performance of the bank and contributes in minimizing the risk.…”
Section: Discussionmentioning
confidence: 99%